Technological Advancement in Housing Industry: A study on the impact of technological advancements in the housing industry (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The scenario of housing industry is being changing rapidly, as the urban population is increasing day by day leads to increase the demand for housing. The most efficient factor in completion of construction project in terms of speed, cost, quality, and safety of work by using the technologies adopted in housing. As the contractor has to complete the project in given frame of time by client, as the client wants to use building for the intended purpose as soon as possible. The most efficient way to speed up the work in mass housing construction is by adopting the new technologies .The aim of this paper is to present the technological transformation adopted in housing industries, to achieve project duration , project cost and quality of work. For that a research has been carried out and the results will present in this paper.